METODE PEMBELAJARAN DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN - Atep Buffa Satria Octariana (Herodotus: Jurnal Pendidikan IPS, 2019)
The purpose of the study was to determine: 1) The Effect of Learning Methods on Learning Outcomes of PPKn Students of State Junior High Schools in North Jakarta. 2) The Influence of Learning Motivation on Learning Outcomes of PPKn Students of State Junior High Schools in North Jakarta. 3) The interactive effect of Learning Methods and Learning Motivation on Learning Outcomes of PPKn students of State Junior High Schools in North Jakarta. The method used in this research is an experimental method with a 2x2 factorial design and the number of samples is 60 students. The results showed that: 1) There is a significant effect of the learning method on the learning outcomes of PPKn students of SMP Negeri in North Jakarta. This is evidenced by the acquisition of sig 0.013 <0.05 and Fcount = 6.626. 2) There is a significant influence of learning motivation on the learning outcomes of PPKn students of SMP Negeri in North Jakarta. This is evidenced by the acquisition of sig 0.003 <0.05 Fcount = 9.898. 3) There is a significant interactive effect of learning methods and learning motivation on the learning outcomes of PPKn students of SMP Negeri in North Jakarta. This is evidenced by the acquisition of sig 0.000 <0.05 and Fcount = 46.559.